Who identifies with the AfD? Explorative analyses in longitudinal perspective - Daniel Baron (Deutsches Institut für Wirtschaftsforschung (DIW), 2018)
Recently, international scholars found two factors that account for partisanship with right-wing populist parties: feelings of economic insecurity and perceived cultural threat. When explaining increasing partisanship with the Alternative für Deutschland (Alternative for Germany, AfD), the first successful right-wing populist party on the state level in Germany, results remain somewhat unclear, especially when it comes to longitudinal analyses. Based on social psychological explanations of party identification and data from the German Socio-Economic Panel 2014 till 2016, this research problem will be tackled throughout this paper. Descriptive analyses show that party identifications among AfD-partisans as well as among partisans of other established parties in the German Bundestag remain stable throughout the observation period. There is a trend of increasing feelings of cultural threat among partisans of all parties, not only of the AfD. To test both explanatory variables, fixed effects and pooled OLS-regressions were used. Only the cultural threat indicator proves to be a significant predictor for strong identification with the AfD.
Keywords: 330; party identification; economic insecurity; perceived cultural threat; right-wing populism; panel analysis; political orientations; partisanship